The effect of “Liposan-3C” preparation on contaits of PUFA in the liver of rats, receiving a fat-free diet - Dvulit, I. P. (Journal of Education, Health and Sport, 2019)
Background. To determine the effect of the PUFA preparation on the content of essential fatty acids in the liver lipids of rats receiving a fat-free diet (FFD).Methods. The preparation “Liposan-3C” was used, containing a composition of fish oil, high oleic sunflower oil, β-carotene and tocopherol adsorbed on silica gel. Rats received with food (FFD) 0.5% or 1.0% of the drug for 22 days. The changes in rat live weight, feed intake and PUFA content in neutral lipids (triglycerides + cholesterol esters) and in the fraction of free fatty acids were evaluated.Results. A 2-fold increase in weight gain was established in rats treated with Liposan-3C. In liver lipids, a decrease in the content of ω-6 PUFA and an increase in the content of ω-3 PUFA were found. The ration with the introduction of 0.5% Liposan turned out to be more effective, and when converted to PUFA with the introduction of 5.38 mg / kg. The ratio of ω-6 / ω-3 PUFA in liver lipids decreased by 2-3 times.Conclusion. The new strew form of essential fatty acids, the drug "Liposan-3C" is an effective means to eliminate the deficiency of ω-3 fatty acids.